(untitled) - Irvine, John (New York, 1988)
This book presents the findings of a recently completed study which surveys the methods and techniques used to evaluate applied research in Japan.
Keywords: Research,Nghiên cứu; Evaluation,Giá trị; Japan,Nhật Bản